Helicobacter pylori Modulated Host Immunity in Gastric Cancer Patients With S-1 Adjuvant Chemotherapy. (19th April 2022) - Koizumi, Yuka; Ahmad, Sheny; Ikeda, Miyuki; Yashima-Abo, Akiko; Espina, Ginny; Sugimoto, Ryo; Sugai, Tamotsu; Iwaya, Takeshi; Tamura, Gen; Koeda, Keisuke; Liotta, Lance A; Takahashi, Fumiaki; et al.
Abstract: Background: Paradoxically, Helicobacter pylori– positive (HP + ) advanced gastric cancer patients have a better prognosis than those who are HP–negative (HP - ). Immunologic and statistical analyses can be used to verify whether systemic mechanisms modulated by HP are involved in this more favorable outcome. Methods: A total of 658 advanced gastric cancer patients who underwent gastrectomy were enrolled. HP infection, mismatch repair, programmed death–ligand 1 (PD-L1) and CD4/CD8 proteins, and microsatellite instability were analyzed. Overall survival (OS) and relapse-free survival (RFS) rates were analyzed after stratifying clinicopathological factors. Cox proportional hazards regression analysis was performed to identify independent prognostic factors. Results: Among 491 patients that were analyzed, 175 (36%) and 316 (64%) patients were HP + and HP −, respectively. Analysis of RFS indicated an interaction of HP status among the subgroups for S-1 dose ( Pinteraction = .049) and PD-L1 ( P = .02). HP + patients in the PD-L1 - group had statistically higher 5-year OS and RFS than HP - patients (81% vs 68%; P = .0011; hazard ratio [HR] = 0.48, 95% confidence interval [CI] = 0.303 to 0.751, and 76% vs 63%; P = .001; HR = 0.508, 95% CI = 0.335 to 0.771, respectively). The 5-year OS and RFS was also statistically higher for HP + compared with HP - patients in the "PD-L1 - and S-1–r educed" group (86% vs 46%; P = .001; HR = 0.205, 95% CI = 0.07 to 0.602, and 83% vs 34%; P = .001; HR = 0.190, 95% CI = 0.072 to 0.498, respectively). Thus, HP status was identified as one of the most potentially important independent factors to predict prolonged survival. Conclusion: This retrospective study suggests that an HP-modulated host immune system may contribute to prolonged survival in the absence of immune escape mechanisms of gastric cancer.